In-vivo Mice Pre-Implantation Embryo Development after Oral Administration Ethanolic Extract of Cogon Grass Roots (Imperata cylindrica L) - Sudiman, Jaqueline; Widyastuti, Rini; Priscilla, Madeline; Lubis, Alkaustariyah; Syamsunarno, Mas Rizky Anggun Adipurna; Sumarsono, Sony Heru (Jurnal Veteriner, 2021)
Cogon grass (Imperata cylindrica L) is known as a medicinal plant that is scattered almost worldwide. Despite its role that inhibits another plant’s growth, cogon grass possesses several benefits in health. This research has to identify the effect of short-term gavage ethanolic extract of cogon grass roots (CGG) to in-vivo mice preimplantation embryo development. A total of 60 female mice were divided into control and treatment groups, dosages at 90 and 115 mg/kg of body weight of CGG, orally gavage for 20 days. The superovulation of mice was done at the end of the CGG treatment by injecting 5 IU Pregnant Mare Serum Gonadotropin (PMSG) and after 48 hours, followed by 5 IU Human Chorionic Gonadotropin (hCG) injection and directly the mice were mated. The mating rate was checked by the appearance of the vaginal plug 12 hours after hCG injection. Mice were sacrificed, the oviducts and cornua of uteri were isolated to collect the oocytes and embryonic cells by flushing the oviducts and cornua uteri with Phosphate-buffered saline (PBS). The effects of CGG as an antifertility were evaluated by measuring the number of oocytes, fertilization, and in-vitro embryo development rates. The results showed significantly reduced about half of the mating rate in the 115 mg/kg BW group (p<0.05) compared to control. However, the 90 mg/kg BW dose reduced 20% mating rate compared to control, and not significant (p>0.05). In all treatment groups, only half oocytes fertilized. The cleavage and blastocyst rate in 115 mg/kg BW group were significantly lower compared to the control group (p<0.05). In conclusion, oral gavage of cogon grass root ethanolic extract disrupts the mating process and development of in-vivo mice preimplantation embryo development.